Learning Electric Circuits Using the STEM Approach to Improve Scientific Thinking Skills and Practice - Haryadi, Rudi; Pujiastuti, Heni (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to determine the effectiveness of using the STEM approach in learning direct electric circuits to achieve high school students' scientific and practical thinking skills. This research is a quasi-experimental method. This study used two class groups, namely the experimental class and the control class, with the experimental class being the class group that received the STEM learning treatment. In contrast, the control class was the class group that only received the immediate learning model treatment. The research design uses a non-equivalent control group design. The research was carried out in the even semester of 2021-2022 and the place of this research was one of the schools in Serang City, Banten province. The sample consisted of two classes; one class was given the learning treatment with the STEM approach, which served as the experimental class, and the other class received no therapy and functioned as the control class. Each course has 40 students, including 20 male and 20 female students. The average age of students is 17 years. The instrument used in this study was in the form of 10 essay questions. This question covered electric current circuit material with indicators of scientific thinking ability and practice. The instrument used in this study was in the form of 10 essay questions. This question covered electric current circuit material with indicators of scientific thinking ability and practice. The data obtained after the research will be analyzed using N-Gain data analysis. The N-gain result in the experimental class was 0.67, while the control class was 0.46. The N-Gain results of the two types show the same category, namely the good category. However, the N-gain results from the experimental class show a value greater than 21% than the control class. These results prove that learning electric circuits using STEM is more effective than learning directly. The implications of this research are 1) It can foster an understanding of the relationship between the concept of electric circuits with practical skills in assembling electric current circuits, 2) Arouse students' curiosity and activate creative imagination and critical thinking, 3) Help students to understand and experiment with the scientific process.